OPTIMIZING TECHNICAL AND ECONOMIC EFFICIENCY: PLASTIC PACKAGING ANALYSIS FOR MINIMIZING VEGETABLE LOSSES AT MOJOSARI MARKET IN MOJOKERTO DISTRICT - Wibowo, Radon Henry; Patiung, Markus; Sastrywanto, Hary (PT. Sangadji Media Publishing, 2024)
The study aimed to assess the technical and economic impact of plastic packaging on reducing vegetable yield losses and enhancing economic value. Conducted in Mojokerto at room temperature using research materials sourced deliberately from the Mojosari market, both primary and secondary data were collected through observation. Technical efficiency was analyzed by calculating the KHS ratio, alongside economic efficiency analysis. Results showed a significant reduction in Vegetable Yield Losses with plastic packaging: mustard (0.403%), carrots (1.352%), and beans (1.826%) compared to treatments without plastic packaging: carrots (49.862%), beans (50.575%), and mustard (51.159%). Plastic packaging demonstrated superior technical efficiency in vegetable storage. Economically, the use of plastic packaging maintained higher economic values for vegetables: mustard (Rp. 4.980,-), carrots (Rp. 4.932,-), and beans (Rp. 4.909,-), compared to treatments without plastic packaging: carrots (Rp. 501,-), beans (Rp. 494,-), and mustard (Rp. 488,-). Thus, plastic packaging proved to be both technically and economically efficient in preserving horticultural vegetables.